Settlements in Brazilian civil public actions: limits and possibilities of consensus after the 2015 Civil Procedure Code and the mediation act DOI:10.5935/2448-0517.20180023 - de Pinho, Humberto Dalla Bernardina (Juris Poiesis - Qualis A3, 2018)
The text seeks to demonstrate how Brazilian legislation has evolved along the way to allowing and making feasible settlements in collective issues. Moving away from a notion of an absolutely unavailable public right, Brazilian lawmaker has prioritized a consensual solution to disputes, even in the public and class sphere. This transition has been materialized, principally, by the undertaking of adjustment of conduct and public mediation. However, at this moment, it is important to set certain limits, so as not to lose sight of legal security and objective parameters to the settlements.